Pendampingan Pembuatan Desain Logo untuk Penguatan Citra Usaha Mikro - Novi Fitri Hermati; Andri Kurnia; M. Irham Ramadhan (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, especially in job creation and income distribution. Despite this, many MSMEs face challenges in building a strong and professional brand image. One of the efforts to overcome these problems is through assistance in logo design. The logo serves as a visual identity that can strengthen the brand's position in the minds of consumers. This study aims to analyze the effect of logo design assistance on strengthening the image of micro businesses. The method used is a literature study of various scientific journals and community service reports in Indonesia that are relevant to this topic. The study results show that logo design assistance is able to increase brand awareness, consumer confidence, and encourage increased sales of MSME products. Thus, graphic design assistance programs such as logos can be an effective strategy in improving the competitiveness and sustainability of MSMEs in local and global markets.